Tinjauan Yuridis Problematika Eksekusi Putusan Wanprestasi : (Studi: 2/Pdt.G/2025/PN Mad Jo. 470/PDT/2025/PT SBY) - Aisha Sofia Chandra Maharani Aisha Sofia Chandra Maharani; Wiwin Yulianingsih Wiwin Yulianingsih (Journal Kompilasi Hukum, 2026)
This study provides a legal analysis of the enforcement of court decisions in cases of breach of contract involving land title certificates. This study aims to analyze the judges’ legal reasoning in adjudicating the breach of contract case regarding the handover of a land title certificate in Judgment No. 2/Pdt.G/2025/PN Mad in conjunction with Judgment No. 470/PDT/2025/PT SBY, as well as the enforcement mechanisms available to the parties in such cases. The research method employed a normative legal approach using statutory, case-based, and conceptual approaches. The results indicate that the condemnatory order issued by the judge was appropriate; however, the validity of the subject matter of the agreement was not analyzed in depth, thereby affecting the enforceability of the judgment. The fact that the certificate is being used as collateral for a security interest by a third party opens the possibility of derden verzet under Article 195(6) of the HIR, while the rejection of the dwangsom removes the financial pressure on the defendant. If enforcement through aanmaning (Art. 195 in conjunction with Art. 196 of the HIR) is not carried out, the plaintiffs may pursue Art. 225 of the HIR as an alternative to convert the obligation to deliver into an equivalent sum of money. Kata kunci: Dwangsom; Eksekusi Putusan; Sertifikat Hak Milik; Wanprestasi.